Tobacco and Antiretrovirals Modulate Transporter, Metabolic Enzyme, and Antioxidant Enzyme Expression and Function in Polarized Macrophages - Mu, Ying; Patters, Benjamin J.; Midde, Narasimha M.; He, Hui; Kumar, Santosh; Cory, Theodore J. (Current HIV Research, 2018)
Background: Cigarette smoking increases systemic oxidative stress, inflammation, and viral replication in individuals with HIV. Macrophages are infected during HIV infection and serve as an important reservoir throughout the process. Macrophages exist in two phenotypes, the classically activated M1 macrophage and alternatively activated M2 macrophage. The expression of drug efflux transporters and metabolic enzymes, which have direct effects on intracellular drug concentrations, differ between the pro-inflammatory M1 macrophage and the anti-inflammatory M2 macrophage. Objective: To further explain the role of tobacco use in worsened outcomes in the HIV + population receiving antiretroviral therapy. Methods: Western blotting was used to examine macrophage polarization and expression of drug efflux transporters, CYP enzymes, and antioxidant enzymes. The arginase assay was used to measure arginase activity. Cytokine production was measured using the human multiplex inflammatory cytokine assay kit. The 8-OHdG DNA Damage Quantification Direct Kit was used to quantify DNA damage. Viral replication under the influence of tobacco and antiretroviral drug use was measured by p24 Elisa. Results: We observed phenotypic shifts from M1 to M2 with both individual and combination treatments with cigarette smoke condensate and the protease inhibitor antiretroviral drug lopinavir. These shifts lead to changes in cytokine production, the expression of CYP enzymes, anti-oxidant enzymes, and drug efflux transporters, as well as changes in viral replication. Conclusion: This data suggest a mechanism by which tobacco use impairs HIV antiretroviral therapy to increase intracellular drug concentrations in this important cellular reservoir.
Keywords: oxidative stress